Mesoamérica en el posclásico: el contexto imprescindible - Rojas, José Luis de (El Colegio de México, A.C., 2005)
Based on an article  by Michael  E. Smith  published in Mexicon in 2003, to celebrate the journal's 25th anniversary, the author reviews sorne characteristics of the studies on Mesoamerica, points out a few of their  problems, and insists on the importance of referring to the  Mesoamerican area  when  carrying out  case stud ies, in order to  avoid current discordances in  the explanations about  Mesoamerican evolution.